2016
DOI: 10.1186/s13071-016-1334-7
|View full text |Cite
|
Sign up to set email alerts
|

Vector-borne transmission of Trypanosoma cruzi among captive Neotropical primates in a Brazilian zoo

Abstract: BackgroundNeotropical primates are important sylvatic hosts of Trypanosoma cruzi, the etiological agent of Chagas disease. Infection is often subclinical, but severe disease has been described in both free-ranging and captive primates. Panstrongylus megistus, a major T. cruzi vector, was found infesting a small-primate unit at Brasília zoo (ZooB), Brazil. ZooB lies close to a gallery-forest patch where T. cruzi circulates naturally. Here, we combine parasitological and molecular methods to investigate a focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
(49 reference statements)
2
16
0
1
Order By: Relevance
“…Fernandes et al (1999) also reported specimens of L. rosalia infected with 'TcII' (without determination of TcIIa-e subgroup) in Rio de Janeiro state (Brazil). Recently, among captive Neotropical primates in a Brazilian zoo, TcI was reported associated with Panstrongylus species transmission (MINUZZI-SOUZA et al, 2016). T. cruzi isolates from lemurs in the United States were assigned to TcIV (HALL et al, 2007;ROELLIG & YABSLEY, 2010) as well as isolates from wild primates in Bolivia and Venezuela (WESTENBERGER et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al (1999) also reported specimens of L. rosalia infected with 'TcII' (without determination of TcIIa-e subgroup) in Rio de Janeiro state (Brazil). Recently, among captive Neotropical primates in a Brazilian zoo, TcI was reported associated with Panstrongylus species transmission (MINUZZI-SOUZA et al, 2016). T. cruzi isolates from lemurs in the United States were assigned to TcIV (HALL et al, 2007;ROELLIG & YABSLEY, 2010) as well as isolates from wild primates in Bolivia and Venezuela (WESTENBERGER et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of more severe changes may be due to a lesser pathology produced by the parasite as a result of the longer evolutionary relationship between parasite and primate host, but may also be related to a fitness cost for the animals, causing them to die before these changes are detected, either by predation or by an inability to cope in nature [45]. In the course of conservation programmes wild species are frequently translocated and, in light of the findings here indicative of both TcII and TcV/VI infection in lion tamarins, it is important to do this in a responsible manner to avoid introducing new parasite populations to non-endemic regions [34, 46]. Infections have also been recorded in captive populations, with an active transmission cycle involving Panstrongylus megistus being identified in a Brazilian Zoo, which is probably an extension of that of a neighbouring intact forest fragment [46].…”
Section: Discussionmentioning
confidence: 99%
“…In the course of conservation programmes wild species are frequently translocated and, in light of the findings here indicative of both TcII and TcV/VI infection in lion tamarins, it is important to do this in a responsible manner to avoid introducing new parasite populations to non-endemic regions [34, 46]. Infections have also been recorded in captive populations, with an active transmission cycle involving Panstrongylus megistus being identified in a Brazilian Zoo, which is probably an extension of that of a neighbouring intact forest fragment [46]. This not only highlights the potential for primates to act as sources of infection for humans, but also the potential for sylvatic triatomines to invade other settings where they are in close contact, such as human settlements at forest edges.…”
Section: Discussionmentioning
confidence: 99%
“…Trypanosoma cruzi infection was investigated by optical microscopy in live bugs at the laboratory as described by Minuzzi-Souza et al 8 . Bugs from LACEN in Goiás were brought dead to MPVBL, precluding fresh-slide examination.…”
Section: Synanthropic Triatomines As Potential Vectors Of Trypanosomamentioning
confidence: 99%
“…House invasion and colonization by P. megistus must hence be closely monitored in areas with gallery forest remnants -and particularly over the early rainy season, when the records of the species in human environments peak 6 . Autochthonous T. cruzi transmission mediated by P. megistus was recently reported in primate units at the Brasília zoo 8 . In spite of the presence of T. cruzi-infected triatomines inside houses, no autochthonous cases of human Chagas disease have so far been reported from the Federal District.…”
mentioning
confidence: 93%